TAWHID-BASED ISLAMIC EDUCATIONAL LEADERSHIP MODEL IN IMPROVING THE QUALITY OF EDUCATIONAL INSTITUTIONS - Nadya Fitri; Syaiful Kiram; Maksudin; Daklan Zuldi Putra Ras (STKIP Subang, 2026)
Improving the quality of Islamic educational institutions requires leadership that is not only managerially effective but also grounded in spiritual values. Tawhid-based leadership is relevant because it integrates Islamic values with quality management practices in educational institutions. This article aims to formulate a tawhid-based Islamic educational leadership model for improving the quality of educational institutions. This study employs a qualitative approach using library research. Data were collected through documentation studies of relevant books and scientific articles and were analyzed using content analysis techniques through the stages of data reduction, categorization, and interpretation. The findings show that tawhid values, manifested through the qualities of Siddiq, Amanah, Tabligh, and Fathonah, form prophetic, Islamic transformational, and Islamic spiritual leadership models. The implementation of these models contributes to institutional quality improvement through the strengthening of human resources, Islamic quality culture, and accountable governance. Therefore, tawhid-based leadership serves as a relevant conceptual framework for improving the quality of Islamic educational institutions in a sustainable manner.